An Analysis of the Implementation of Sexual Violence Prevention and Response Policies (PPKS) in Higher Education in Indonesian - Pambudi, Abdul Rachman; Sutrisno, Edy; Rivai, Firman Hadi (Ilomata International Journal of Social Science, 2025)
Sexual violence in higher education is a systemic issue that threatens student safety and academic well-being. Although 77% of Sexual violence in higher education is a systemic issue that endangers student safety and academic well-being. Although 77% of lecturers acknowledge its occurrence, 63% of cases go unreported, revealing significant institutional gaps. In response, the Indonesian Ministry of Education introduced the Regulation on the Prevention and Handling of Sexual Violence in Higher Education (PPKS). While prior studies have explored the prevalence of such violence, few have assessed policy implementation using a structured theoretical framework. This study applies the Mazmanian and Sabatier implementation model to analyze institutional and systemic challenges and propose evidence-based strategies. Using a descriptive qualitative approach, the study combines document analysis with in-depth interviews involving national policymakers and stakeholders from five purposively selected universities. Selection criteria reflect institutional diversity, geographic spread, and variation in PPKS best practices. The findings highlight ongoing challenges, including the absence of structural task force integration, limited human resource capacity, insufficient budget support, and low awareness and literacy regarding sexual violence. To address these barriers, the study proposes three strategic directions: (1) strengthening institutional mandates and issuing national technical regulations; (2) transforming campus culture through curriculum reform and multi-stakeholder collaboration; and (3) ensuring sustainability through capacity building, peer learning among task forces, and performance-based evaluation mechanisms. The study concludes that overcoming structural and cultural constraints is essential for effective implementation and that coordinated efforts are needed to create safer, more inclusive higher education environments.